Tinjauan Kriminologi Terhadap Tindak Pidana Penyerobotan Tanah (Studi Kasus di Wilayah Hukum Polda Gorontalo) - Frieska Jayanthy Datau (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
The type of research used is empirical legal research, a qualitative approach. The research sample is the Gorontalo Regional Police, as well as the people who have disputes over land grabbing. The data obtained through primary and secondary data were analyzed qualitatively to be presented descriptively. The results of the study show that the cause of land grabbing which continues in legal proceedings in the jurisdiction of the Gorontalo Regional Police is the desire to own or control land based on ownership claims which are inherited land owned by parents. The handling of criminal acts of land grabbing by the Gorontalo Regional Police includes educating the public with the cooperation of the local government, commitment to investigate and prosecute perpetrators, strengthen the law through imposition of sanctions with a deterrent effect, and collaborate to strengthen the land registration system. The inhibiting factors experienced by the Gorontalo Regional Police in handling the criminal act of land grabbing include the weakness of legal substance and the hassle of legal procedures and difficulties in summoning witnesses and experts.